Greywater treatment using pottery waste ceramic filter - Radin Maya Saphira Radin Mohamed,; Al-Gheethi, Adel; Nasradeen A . Khalifa,; Nurina Fitriani,; Adeleke, Abdurrahman; Ebenehi, Ibraheem Yakubu; Siti Asmah Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Most village houses in Malaysia discharged lots of significant portion of greywater into stream or drains without any treatment. This phenomenon of direct disposal of greywater into the environment caused environmental risk, especially to water body. This study aimed to assess the quality and treatment of greywater discharge using pottery waste ceramic filter (PWCF) for safe disposal. Greywater samples were collected from 27 village households located at Kampung Parit Sempadan, Parit Raja using grab sampling method. Greywater was treated by using PWCF. The effectiveness of the PWCF was optimized using different sizes (0.25, 0.60, and 1.18 mm) of ceramic filter media at different hydraulic retention times (HRT: 1, 2, and 3 h). The t-test analysis showed significant differences between greywater from the two drainage distances. The results revealed that a distance within 81–100 m was significant to the influence of gender and the number of household occupants of the greywater discharged. The results of this study highlight that PWCF reduced the concentration of COD, BOD and TSS in greywater by 99.4%, 74.3 and 100% respectively using particle size of 0.25 mm and HRT of 3 hours. Finally, it deduced that the use of PWCF was effective and can enhance the quality of greywater for safe disposal.